2017
DOI: 10.3389/fcimb.2017.00027
|View full text |Cite
|
Sign up to set email alerts
|

HA Triggers the Switch from MEK1 SUMOylation to Phosphorylation of the ERK Pathway in Influenza A Virus-Infected Cells and Facilitates Its Infection

Abstract: Several post-translational modifications in host cells are hijacked by pathogens to facilitate their propagation. A number of components of the influenza virus have been reported to be modified by small ubiquitin-like modifier (SUMO) proteins during infection. We hypothesized that the MAPK/ERK pathway could be modified by SUMO1 because the SUMOylation of MEK1 was quickly eliminated after influenza A virus infection. We identified host cell MEK1 as a target of SUMO1 through LC/MS/MS, and enhanced MEK1 SUMOylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Recent studies of cellular metabolic processes [ 97 , 98 ] and post-transcriptional protein modification [ 99 , 100 ] identified additional approaches used by viruses to evade host immune responses [ 101 ], and to facilitate optimal replication [ 102 ].…”
Section: Modulation Of Immune Responses Against Respiratory Virus Infmentioning
confidence: 99%
“…Recent studies of cellular metabolic processes [ 97 , 98 ] and post-transcriptional protein modification [ 99 , 100 ] identified additional approaches used by viruses to evade host immune responses [ 101 ], and to facilitate optimal replication [ 102 ].…”
Section: Modulation Of Immune Responses Against Respiratory Virus Infmentioning
confidence: 99%
“…In contrast to many other signaling events in IAV-infected cells, it is not activated by viral RNA (vRNA) sensing via RIG-I but rather is induced by accumulation of newly produced viral hemagglutinin (HA) in lipid rafts in the membrane of infected cells (Marjuki et al, 2006 ). Furthermore, it was recently shown that the presence of HA triggers the switch from MEK1 SUMOylation to an activating phosphorylation leading to the downstream activation of ERK1/2 (Wang et al, 2017 ). Thus, the cascade is implicated to control temporal coordination of virus particle assembly (Marjuki et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…This appears to induce the formation of lipid rafts, which serve as signaling platforms for protein kinase C (PKC)-dependent Raf/MEK/ERK activation, presumably by bringing monomeric receptor molecules in close proximity to each other. Further findings showed that HA triggers a switch from MEK1 SUMOylation to activation of the ERK pathway, thereby enhancing the activity of the cascade (Wang et al 2017).…”
Section: The Classical Map Kinase Cascade (Raf/mek/erk)mentioning
confidence: 94%